PERLINDUNGAN HAK ANAK PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - fitri dalilatun; Nila Amania (Hukum Keluarga Islam, 2024)
Protection of children's rights is often associated in Islamic law with the ethical and spiritual obligations of parents and society. For example, parents have an obligation to ensure that their children receive a quality education and are raised in a safe and caring environment. In contrast, the protection of children's rights in Indonesian positive law focuses primarily on the legal and administrative components, emphasizing the need for clear law enforcement procedures and penalties for those who violate children's rights. A qualitative approach using descriptive-comparative analysis methodology is the research methodology used. The purpose of this study is to determine the positive laws and regulations of Indonesia with Islamic law regulations related to the protection of children's rights. Various teachings on child protection, including those related to the right to life, the right to education, the right to be safe from violence, and the right to welfare, can be found in Islamic law. On the other hand, laws and regulations such as Child Protection Law Number 35 of 2014 have been regulated by positive laws and regulations in Indonesia, providing different protection for children's rights.